Evaluation of nursing students’ diagnoses using the Omaha System - Ateş, Elif; Ulus, Bahire (The European Research Journal, 2019)
Objectives: Nursing process guides the students in the diagnosing, planning, intervention and evaluation of patients/families, and it also gives a systematic point of view. The Omaha System is used as a nursing classification system in public health nursing course practice areas. It was conducted in order to examine the nursing diagnoses identified by the students according to the Omaha System. Methods: It was a retrospective, analytical research. Practice files of 51 students who took the public health nursing course created the sample. Results: According to the Omaha problem classification list (PCL), the students in the study identified a total of 412 problems. According to Omaha PCL, the students mostly used the area of health behavior, followed by the physiological, psychosocial and environmental areas respectively. It was determined that 73% of the students had sufficient skills to use the Omaha System and 26.8% of them were inadequate. Conclusion: It was observed that the nursing diagnoses identified by the students in line with the determined learning targets were sufficient.